2012
DOI: 10.1080/19404476.2012.11462090
|View full text |Cite
|
Sign up to set email alerts
|

Using Simulations to Teach Middle Grades U.S. History in an Age of Accountability

Abstract: In this year-long qualitative study we explore the case of two eighth grade U.S. History teachers who use simulations on a regular basis to teach heterogeneously-grouped students in a high-stakes testing environment. We describe the purposes the teachers espoused for implementing simulations and provide detailed portraits of three types of simulations used: role-play, game, and trial. We argue that because the ambitious teachers know their discipline well, see the potential of all their students, and feel that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Researchers have found that teachers' reasons for employing simulations are varied and often idiosyncratic (Blaga, 1978;DiCamillo & Gradwell, 2012;Ganzler, 2010). Teachers have identified simulations as an effective means of addressing differentiated learning needs and as particularly helpful for both high-performing and low-performing students (DiCamillo & Gradwell, 2012).…”
Section: Defining Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that teachers' reasons for employing simulations are varied and often idiosyncratic (Blaga, 1978;DiCamillo & Gradwell, 2012;Ganzler, 2010). Teachers have identified simulations as an effective means of addressing differentiated learning needs and as particularly helpful for both high-performing and low-performing students (DiCamillo & Gradwell, 2012).…”
Section: Defining Simulationsmentioning
confidence: 99%
“…Teachers have identified simulations as an effective means of addressing differentiated learning needs and as particularly helpful for both high-performing and low-performing students (DiCamillo & Gradwell, 2012). Additionally, simulations are particularly useful for eliciting empathetic responses to the content being taught (Else, 2006;Maitles & McKelvie, 2010), aligning students' perceptions of their abilities with reality (Niv-Solomon et al, 2011), and altering the way students think about when to cooperate or compete (Williams & Williams, 2007).…”
Section: Defining Simulationsmentioning
confidence: 99%
“…A brief search revealed that many recent articles on simulations in social studies coursework deal with history education and simulations as a way for students to better engage and obtain historical information/perspective (e.g. Corbeil & Laveault, 2011;DiCamillo & Gradwell, 2012;Schweber, 2003). At the same time, studies that deal with democratic education tend to involve legislative simulations and focus on students' political knowledge or efficacy at the end of the course (e.g.…”
Section: Best Practices In Social Studies Educationmentioning
confidence: 99%
“…We found the two teachers, Andy Bender and Jim Kramer (all names are pseudonyms), were engaging students in a unique, simulations-based curriculum, so we expanded our research to continue studying their practice and to address the need for more rigorous research on secondary teachers who use simulations. In our expanded study, we explored how the teachers implemented the simulations in their classes, their purposes for using simulations, and supports and challenges they encountered when enacting simulations (DiCamillo and Gradwell 2012). …”
Section: Our Simulation Studymentioning
confidence: 99%